MAPPING AND ASSESSMENT OF TRAFFIC CONGESTION ON MAJOR ROADS IN MINNA (CASE STUDY OF CHANCHAGA L.G.A) - Oluibukun Gbenga Ajayi; Ayodeji Timothy Oluwunmi; Joseph Olayemi Odumosu; Taiwo James Adewale (Geoplanning: Journal of Geomatics and Planning, 2017)
The level of urbanization in the developing world indicates that more people live in cities nowadays than before. As urbanization increases, road usage also proportionately increases which sometimes introduce some strains to the existing road. As a consequence, it constitutes some impediments to free traffic flow. The situation described above is located on Chanchaga Local Government Area of Niger State, an urban center in North central, Nigeria. In order to investigate the probable causes and degree of severity of this menace, attempt has been made in this research to investigate and map out the nature of traffic congestion frequently experienced on some selected roads within Chanchaga LGA. These road networks include: Kpakungu-Gidan Kwano road, Bosso-Mobil route, Bosso–Mekunkele route, Kpakungu–city gate road and Book roundabout–Mobil Route. Using a 1m Pan-Sharpened spatial resolution IKONOS Image, handheld GPS receivers, and manual traffic count, the traffic patterns of the selected road networks within the study area were assessed and mapped out. A Geo-Database was also designed for the routes which provide information about the road pavement condition, average traffic volume, adjacent land use, etc. Analysis of results and other performed queries revealed that the most probable causes of traffic congestion in Chanchaga LGA were due to narrow road width, bad road pavement and indiscriminate parking of vehicles along the road corridors, especially by commercial cab drivers. Conclusively, it was observed that the Kpakungu axis of Minna – Bida road is the most congested route of the entire road networks considered, closely followed by the Bosso-Mobil Road. The traffic gridlock along these routes is most prominent on Mondays and Wednesdays (around 8am and 4pm) and correspondingly on Fridays (around 1-4pm). Furthermore, a free traffic flow is frequently experienced on Saturdays by 8am which gradually builds a synchronized flow around the evening time on all the considered road networks.